Evaluating the safety and the effects on colonic compliance of neostigmine during motility testing in patients with chronic constipation. Issue 6 (3rd February 2016) - Mouchli, M. A.; Camilleri, M.; Lee, T.; Parthasarathy, G.; Vijayvargiya, P.; Halland, M.; Acosta, A.; Bharucha, A. E.
Abstract: Background: Neostigmine, an acetyl cholinesterase inhibitor, stimulates colonic motor activity and may induce vagally mediated cardiovascular effects. Our aim was to evaluate effects of i.v. neostigmine on colonic compliance and its safety in patients with chronic constipation. Methods: We retrospectively reviewed medical records of a selected group of 144 outpatients with chronic constipation who were refractory to treatment. These patients had undergone intracolonic motility and compliance measurements with an infinitely compliant balloon linked to a barostat. Data abstracted included barostat balloon mean volumes with increases in pressure (4 mmHg steps from 0 to 44 mmHg) before and after i.v. neostigmine. Vital signs and oxygen saturation before and after neostigmine were recorded. Key Results: Of the 144 patients, 133 were female, mean age was 41.0 ± 15.4 years (SD), and duration of constipation was 12.9 ± 13.8 years. Among patients who had undergone colonic transit measurement by scintigraphy, the overall colonic transit at 24 h (geometric center, GC24 [ n = 115]) was 1.5 ± 0.7 (normal >1.3), and at 48 h (GC48 [ n = 75]) it was 2.3 ± 0.9 (normal >1.9). Neostigmine decreased colonic compliance at lower distension pressures (e.g., 12 and 20 mmHg [both p < 0.001]), but not at 40 mmHg. There were expected minor changes in vital signs in response to neostigmine in 144 patients; however, one patient developed unresponsiveness, significant bradycardia, hypotension, and muscular rigidity that responded to 400 mcg i.v. atropine. Conclusions & Inferences: Neostigmine significantly decreases colonic compliance in patients with refractory chronic constipation. Symptomatic bradycardia in response to neostigmine should be promptly reversed with atropine. Abstract : We retrospectively reviewed medical records of a selected group of 144 outpatients with chronic constipation who were refractory to treatment. Neostigmine significantly decreases colonic compliance in patients with refractory chronic constipation. Symptomatic bradycardia in response to neostigmine should be promptly reversed with atropine.